Evaluating the long-term impact of an antimicrobial stewardship programme in a Central London mixed medical and surgical intensive care unit. Issue 5 (10th October 2022) - Singh, Shivani; Ark, Rajiv; Tatlock, Jason; Mandalia, Sundhiya; Chung, Christine; Azadian, Berge; Hughes, Stephen; Mughal, Nabeela; Moore, Luke S P; Singh, Suveer
Abstract: Background: Antimicrobial overuse causes increased antimicrobial resistance in ICUs; antimicrobial stewardship programmes (ASPs) aim to optimize usage. Following an MDR Acinetobacter baumannii (MRAb) outbreak in 2008, an ASP was implemented at a London ICU, and then continued as a long-term programme. This study aimed to determine long-term changes in antimicrobial prescribing 9 years on. Methods: Data were collected from ICU patients in 2008 immediately before ASP implementation, and thereafter for 6 month cohort periods in 2010–2011, 2012 and 2017. Antimicrobial usage in DDD per 1000 occupied bed days (OBD) were compared. Multivariate linear regression models for antimicrobial days were fitted, adjusting for APACHE II score and patient days. Antimicrobial resistance in Pseudomonas aeruginosa (as an indicator organism) was compared across cohort periods. Findings: Across 400 patients over 9 years, antimicrobial use changed significantly ( P  < 0.011) and remained lower in all post-ASP cohorts compared with pre-ASP [(2008; 1827 DDD/1000 OBD), (2010; 1264 DDD/1000 OBD), (2012; 1270 DDD/1000 OBD) and (2017; 1566 DDD/1000 OBD)]. There was reduction in usage of all antimicrobial classes except β-lactams (where there was no significant increase nor decrease, P  = 0.178) and aminoglycosides (where there was a significant increase in usage, P  < 0.0001). The latter was temporally associated with restrictions on specific carbapenems. There was an increase in carbapenem-resistant P. aeruginosa in 2012 only ( P  = 0.028) but not subsequently. Conclusions: Following ASP implementation after an outbreak of MRAb, reduced antimicrobial prescribing was maintained 9 years on. We identify several factors influencing successful long-term maintenance of ASPs in ICUs.